PROBLEM OF THE ORIGIN OF SCAPOLITE IN RARE METAL PEGMATITES OF SANGILEN - Kuznetsova L.G.; Sizykh Yu.I. (My University, 2004)
Scapolite is usually known as a mineral of metamorphic rocks and skarns. Primary-magmatic scapolite is extremely rare. This article presents data on the primary scapolite first detected in rare metal pegmatites. The scapolite- and spodumene-bearing vein was found in the Sol'bel'der pegmatite field within the Sangilen Highland, which is well known for its Li-pegmatite deposits. Spodumene pegmatites make up converged and subparallel veins confined to linear fracture zones in the weakly metamorphosed (marbleized) and bituminous limestones. In contrast to the majority of the world's Li-bearing fluid-magmatic systems enclosed in aluminosilicate rocks, the Sangilen rare-metal province is characterized by the intrusion of magmatic melts into a thick carbonate sequence.